Influence of information communication technology on health and behaviour of University of Ibadan undergraduates (2014)
The study examines the influence of Information Communication Technology on health and behaviour of University of Ibadan undergraduates. Descriptive survey research design was adopted to select one thousand and eighty-one students, through stratified and simple random techniques; a self-structured questionnaire with 0.70 reliability coefficient was used for data collection. Six hypotheses were tested and chi-square x2 was used for data analysis at 0.05 level of significance. The results showed that the respondents had no knowledge of the négative effect of ICT on health and behaviour (x-0.67, p<0.05); that ICT has negative influence on respondents' sexual behaviour (x2=84.6, p>0.05), sleeping pattern (x2=68.5, p>0.05), nutrition pattern (x2=56.3, p>0.05), and academic honesty (x2=72.4, p>0.05). However, ICT did not influence their engagement in cybercrime (x2=2.16, p<0.05). Based on the findings it was recommended, among others, that education on the negative influence of ICT use on health and behaviour of students should be included in the general courses for students; and that there should be adequate monitoring of the cyberspace by school authority.